Journey into Islam : the crisis of globalization / Akbar Ahmed. - Ahmed, Akbar S. (Akbar Salahudin), 1943- (Brookings Institution Press, 2007)
"Presents a tour of Islam and its peoples as it follows author's anthropological expedition to the three major regions of the Muslim world--the Middle East, South Asia, and East Asia. Reveals unique information on large, often misunderstood populations, describing the experiences and perceptions of ordinary Muslims, women, and youth"--Provided by publisher